PERAN SISTEM INFORMASI AKUNTANSI DALAM PENGELOLAAN KEUANGAN GEREJA DI GEREJA GPIB IMMANUEL PEKANBARU - Rebeka Manurung; Gusnardi '; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: Based on the Statement of Financial Accounting Standard 45 of 2011 about Non-Profit Organization, the non-profit organizations are obliged to make a financial report and should report on the users of financial report. Church as one of the non-profit organization is obliged to make an accountable financial report as well and report on to the congregation as the member of church which is also the main source of Church’s income and report on to the donators for instance the companies which are giving charity find to the church. Accounting is the activity of recording, classifying, summerizing, reporting, and analyzing the financial report of the organization. Therefore, church need accounting as a tools that help it on making, planning and supervising the accountable and transparent financial report that based on to the Statement of Financial Accounting Standard 45 of 2011 about Non-profit Organization Financial Reporting Standard which is by Accounting Association of Indonesia.Keywords: Accounting, Church Finance, Financial Report.